Medication Reconciliation: Audit to an Internal Medicine Ward - Corrêa Figueira, Mafalda; Brigas, Daniela; Silva, Filipa; Madeira, Margarida; Carneiro, Patrícia; Lobão, Bárbara; Pedroso, Ermelinda (Portuguese Journal Internal Medicine, 2019)
Introduction: Ageing population is characterized by multiple comorbidities, polypharmacy and medication safety vulnerability. Medication discrepancies, together with the inexistence of medication reconciliation procedures that implement National Health Department recommendations, lead to negative consequences as drug interactions, healthcare non-programmed admissions and to geriatric syndromes. Materials and Methods: The authors audited the prevalence of medication reconciliation at discharge, analysing the pharmacological record and identifying discrepancies and errors of medication. As a secondary endpoint, inward patients were characterized. Data was collected through computer record consultation as well as through patient or caregiver interview. Results: Median of age was 78 years and half of patients were totally dependent. There was a 3.9 average of comorbidities, medication reconciliation was present in 47% and in 61% there was at least one medication discrepancy or error. The medication error most frequently encountered was the introduction error. Discussion and Conclusion: The high prevalence of medication discrepancies and of non- medication reconciliation is in part due to the inexistence of a systematic process for collecting pharmacological history, poor doctor-patient communication and the lack of medication reconciliation procedure. The higher prevalence of introduction errors may be due to copy paste of previous and out of date pharmacological records. There is a need for prospective studies that evaluate the medication reconciliation influencing factors, the medication errors and its short and long-term consequences.